Viabilidade das Reservas Particulares do Patrimônio Natural (RPPN): análise legal e administrativa - Gusi, Carol Vosgerau (2021)
Within the Conservation Unit categories contemplated in Brazilian and international legislation, Private Reserves of Natural Heritage (RPPN) are legally protected spaces of sustainable use that aim to promote environmental conservation. The fomentation of this protected area category is intrinsically related to the private initiative, considering that the creation of an RPPN, even though it is instituted by an act of public power, depends on the will of the landowner. After the registration in the property legal document, it is up to the owner or manager of the reserve to administrate it in an appropriate and harmonious way, in order to avoid economic losses for himself and damage to the environmental resources of the place. Legislation, as a source of guidelines and regulations on RPPN, safeguards the power to facilitate or hinder this process and the expansion of private reserves in Brazil. Likewise, environmental agencies and administrative regulations are crucial for the creation of the reserve and its subsequent inspection to be feasible. Inside this theme of protected areas, this research strives to answer the question: Is the RPPN a viable instrument for conservation? Considering both the viability of the RPPN to the System of Conservation Units (SNUC) and to the land owner. The general objective, therefore, is to analyze the viability of this type of reserve and, for this, a qualitative/quantitative methodology was chosen, built through a critical and analytical study of the current legislation and the behavior of environmental administrative bodies. The analysis is complemented with a case study of the creation of a RPPN in the rural region of the Municipality of Palmeira, Paraná, which brings rich information and recommendations about the process experienced. Inserted in the Line B of research (Planning, Conservation and Social and Environmental Development) and associated with the Planning Project and Implementation of Environmental Management Proposals, this study provides sufficient data and foundations to conclude that the RPPN is viable as a voluntary environmental conservation tool by individuals. This viability, however, is conditioned to the active support work of environmental agencies, economic incentives and dissemination of environmental and social benefits for the surrounding community. With this in mind, regulatory changes and ways to develop private reserves are proposed so that they do not fall into disuse.